Building triple shelled ZnO hollow microspheres decorated TiO2 nanotree to boost light harvesting and reduced charges recombination in dye sensitized solar cell. (October 2022) - Yu, Libo; Li, Zhen
Abstract: It is well known that the microstructure of photoanode materials has direct influence on light harvesting and charges recombination in dye sensitized solar cells (DSSC). However, design of photoanode materials for efficient light harvesting and electron transport is still in challenge. Therefore, we developed a hierarchical microstructure of multi shelled ZnO hollow microspheres (MS ZnO HMS) decorated TiO2 nanotree (NT) for DSSCs application with aim to take advantages of enhanced light scattering and enlarged specific area offered by MS ZnO HMS and reduced charges recombination provide by TiO2 NT. The morphology, microstructure and crystalline of ZnO HMS and TiO2 NT have been characterized by SEM, TEM and XRD, confirming the successful building of MS ZnO HMS decorated TiO2 NT. I–V tests show that significant enhancement of short-circuit current density (Jsc ) can be achieved by controlling shell numbers of MS ZnO HMS and combining MS ZnO HMS with TiO2 NT. As a result, the triple shelled ZnO HMS (TS ZnO HMS) decorated TiO2 NT (TS ZnO HMS/TiO2 NT) improve the power conversion efficiency (PCE) to 7.40%, which is 138% and 40% higher than DSSCs based on TiO2 NT (3.11%) and TS ZnO HMS (5.27%). IPCE, OCVD and EIS measurements indicate that the combination of TS ZnO HMS with TiO2 NT contribute to the improvement of light harvesting efficiency and prolonging of electron lifetime. Graphical abstract: Image 1 Highlights: Multi shelled ZnO hollow microspheres decorated TiO2 nanotree have been built. Enhanced light harvesting and electron transport occurred with this structure. Controlling shell numbers of ZnO hollow microspheres improve light harvesting. TiO2 nanotree underlayer facilitate electrons transport prolong electron lifetime. PCE achieved with this structure is 138% higher than TiO2 nanotree based DSSC.